URGENSI ONLINE DISPUTE RESOLUTION SEBAGAI BENTUK PENYELESAIAN SENGKETA DI ERA SOCIETY 5.0 - Rivaldo Fariadi Ivanda; Shelvi Rusdiana (Program Studi Ilmu Hukum, Jurusan Hukum dan Kewarganegaraan, Fakultas Hukum dan Ilmu Sosial, Universitas Pendidikan Ganesha, 2023)
The era of society 5.0 is an era where information technology and humanities run simultaneously, the presence of technology in a developing society with the presence of laws that adjust to form a harmony and renewal that brings progress to Indonesia, one of which is the presence of online dispute resolution as a form of dispute resolution that is make it easier not only for entrepreneurs but for consumers who are in dispute. The presence of ODR in Indonesia is a necessity for the community due to the increasing number of people interacting with the internet, this is also encouraged as a form of efficiency both in terms of time and cost. ODR which is developing in Indonesia is also supported as an online dispute resolution with the presence of the ITE Law, Government Regulation of Trading through ES and the AADR Law. Research conducted by researchers using normative methods by collecting data qualitatively and utilizing documents, journals, books, and laws and regulations as a form of research elaboration. The data sources used are secondary data sources using writings, dictionaries and regulations as basic references. This study aims to determine the urgency of the presence of the Arbitration Law and Alternative Dispute Resolution which can be the basis for implementing Online Dispute Resolution in Indonesia, but there is a need for a law that specifically regulates this ODR so that it can focus more on disputes and their regulation